2011
DOI: 10.1590/s1516-35982011000500026
|View full text |Cite
|
Sign up to set email alerts
|

Intake, apparent nutrient digestibility and ingestive behavior of sheep fed cashew nut meal

Abstract: -The objective of this work was to evaluate intake, nutrient apparent digestibility and ingestive behavior of sheep fed rations with cashew nut meal (CNM) at the levels of 0; 10; 20 and 30% in the concentrate ration. It was used a double 4 × 4 Latin square experimental design. Intakes of dry matter (DM), organic matter, crude protein, mineral matter, non-fibrous carbohydrates and total digestible nutrients were not influenced by the addition of CNM, however, intake of neutral detergent fiber (NDF), acid deterg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Pimentel et al (2011) found that the AD of DM, CP, NDF, and ADF were not influenced by addition of CNM to the diets. Teles et al (2010) observed an increasing linear response of NB to inclusion of dried cashew apple in the ensilage of elephant grass.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Pimentel et al (2011) found that the AD of DM, CP, NDF, and ADF were not influenced by addition of CNM to the diets. Teles et al (2010) observed an increasing linear response of NB to inclusion of dried cashew apple in the ensilage of elephant grass.…”
Section: Discussionmentioning
confidence: 85%
“…Pimentel et al (2011) evaluated the intake of nutrients in sheep fed diets containing cashew nut meal (CNM) at the levels of 0, 100.0, 200.0, and 300.0 g kg -1 of the concentrated diet. Neither dry matter nor crude protein intake was influenced by addition of CNM; however, the intakes of NDF and ADF showed a quadratic response to the increase in the dietary lipid level.…”
Section: Discussionmentioning
confidence: 99%
“…This finding might be explained by the high content of polyunsaturated fatty acids in the meal and mass of these feed constituents (PiMenTel et al, 2011), while the lower digestibility observed for ACF could be associated with the higher proportion of tannins and the fibrous fraction in the almond film (aRRuda et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, the almond cashew nut meal is composed of whole almonds and parts that are not suitable for human consumption (PiMenTel et al, 2011), while the almond cashew nut film originates from the skimming and processing of this kernel for human consumption and the mass is derived from the production of biofuel through mechanical extraction (FeRnandes, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, in all environments feed characteristics influence animals' motivation to eat, dietary choices and, ultimately, nutrient intake (Baumont et al, 2000;Haddad, 2005;Luo et al, 2000;Pimentel et al, 2011). In all production systems, it is generally economically sensible to maximize the proportion of forage in the diet to minimize feeding costs.…”
Section: Introductionmentioning
confidence: 99%